Appropriate attenuation model for Chiang Mai, Thailand from field measurement to model equation - Tawatchai Tanchaisawat (2018)
© Int. J. of GEOMATE. Earthquake occurs frequently in Thailand especially in upper norther part in past 5 years ago. Thailand has also many fault, especially upper northern. The upper northern part may risk by earthquake. The earthquakes damage of buildings or people and these damages will depend on peak ground acceleration (PGA). Peak ground acceleration (PGA) is an important factor for analysis and design of building or related structure on top. This study was analyzed earthquake attenuation model of group Next Generation Attenuation Models (NGA) and Stable Continental Region. First group, the model was listed as Abrahamson and Silva (2008) and Idriss (2008). For the second group, the model was listed as Toro et al. (1997), Hwang and Huo (1997) and Dahle et al. (1995). Each model analysis was done by using the earthquake intensity that had happened according to the earthquake that detected from field measurement of 6.3 Richter scale on May 5th 2014. The epicenter was in Mae Lao district, Chiang Rai province in northern of Thailand. The result of this research was summarized by mean of peak ground acceleration (PGA) between the attenuation models and the field data measurement by checking the accuracy of each model. It can be concluded that the attenuation model of Abrahamson and Silva (2008) give more accurate acceleration data compare to other models.